2019
DOI: 10.1002/ccd.28409
|View full text |Cite
|
Sign up to set email alerts
|

Use of 65 cm large caliber Dryseal sheaths to facilitate delivery of the Edwards SAPIEN valve to dysfunctional right ventricular outflow tracts

Abstract: Background The Edwards SAPIEN valve and its delivery system may complicate transit through the right heart during transcatheter pulmonary valve replacement (tPVR). We report our early experience using a large diameter, 65 cm delivery sheath to facilitate delivery of the SAPIEN valve to the right ventricular outflow tract (RVOT). Methods Retrospective analysis of all patients from three large congenital heart centers undergoing tPVR with the Edwards SAPIEN valve delivered with the 65 cm Gore Dryseal Sheath. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 11 publications
(20 reference statements)
0
22
0
1
Order By: Relevance
“…Recently, the modified delivery technique using the 65-cm DrySeal sheath instead of the short e-sheath has been reported. 13,14 The tip of the DrySeal sheath can quite easily be advanced into the distal main pulmonary artery and allows for rapid advancement and coverage of the Sapien valve to the pulmonary position. These studies demonstrated that this technique can facilitate valve delivery and potentially prevent tricuspid valve injury.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, the modified delivery technique using the 65-cm DrySeal sheath instead of the short e-sheath has been reported. 13,14 The tip of the DrySeal sheath can quite easily be advanced into the distal main pulmonary artery and allows for rapid advancement and coverage of the Sapien valve to the pulmonary position. These studies demonstrated that this technique can facilitate valve delivery and potentially prevent tricuspid valve injury.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have noted use of the DrySeal sheath in a patient who weighed 23.8 kg. 13 We acknowledge several limitations related to the design of this study. As this study was conducted at an experienced single center, the results may not be generalizable for all practices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Positioning the sheath in the mid left ventricle across the mitral orifice provided hemodynamic stability, relatively easy passage of the valve antegrade and protected the mitral valve apparatus from impingement, injury, or entanglement by the wire and valve delivery system. This technique is analogous to utilization of the DrySeal sheath for tricuspid valve protection during implantation of the SAPIEN valve in the pulmonary position 5 . The patient remained hemodynamically stable with the sheath across the mitral valve orifice allowing the procedure to be performed in an unhurried manner.…”
Section: Discussionmentioning
confidence: 99%